Planktonic and benthic foraminifera, benthic foraminiferal stable isotopes, sedimentary organic and inorganic carbon and opal, age model and trace elements of IODP Hole 344-U1381C - Diz, Paula; Hernández-Almeida, Iván; Bernárdez, Patricia; Pérez-Arlucea, Marta; Hall, Ian R (PANGAEA, 2024)
This bundle publication contains six individual datasets of micropaleontological data (planktonic and benthic foraminiferal assemblages), geochemical data (sedimentary organic and inorganic carbon, opal and major and minor elements) measured in IODP Hole 344-U1381C. The records span the last 780 ka according to the age model.
Keywords: nitrogen content; opal; Organic carbon